Characterization and comparison of fatty acyl Delta 6 desaturase cDNAs from freshwater and marine teleost fish species - Zheng, Xiaozhong; Seiliez, Iban; Hastings, Nicola; Tocher, Douglas R; Panserat, Stephane; Dickson, Cathryn; Bergot, Pierre (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2004)
Fish are the most important dietary source of the n-3 highly unsaturated fatty acids (HUFA), eicosapentaenoic (EPA) and docosahexaenoic acid (DHA), that have particularly important roles in human nutrition reflecting their roles in critical physiological processes. The objective of the study described here was to clone, functionally characterise and compare expressed fatty acid desaturase genes involved in the production of EPA and DHA in freshwater and marine teleost fish species. Putative fatty acid desaturase cDNAs were isolated and cloned from common carp (Cyprinus carpio) and turbot (Psetta maximus). The enzymic activities of the products of these cDNAs, together with those of cDNAs previously cloned from rainbow trout (Oncorhynchus mykiss) and gilthead seabream (Sparus aurata), were determined by heterologous expression in the yeast Saccharomyces cerevisiae. The carp and turbot desaturase cDNAs included open reading frames of 1335 and 1338 base pairs, respectively, specifying proteins of 444 and 445 amino acids. The protein sequences possessed all the characteristic features of microsomal fatty acid desaturases, including three histidine boxes, two transmembrane regions, and N-terminal cytochrome b5 domains containing the haem-binding motif, HPGG. Functional expression showed all four fish cDNAs encode basically unifunctional Δ6 fatty acid desaturase enzymes responsible for the first and rate-limiting step in the biosynthesis of HUFA from 18:3n-3 and 18:2n-6. All the fish desaturases were more active towards the n-3 substrate with 59.5%, 31.5%, 23.1% and 7.0% of 18:3n-3 being converted to 18:4n-3 in the case of turbot, trout, seabream and carp, respectively. The enzymes also showed very low, probably physiologically insignificant, levels of Δ5 desaturase activity, but none of the products showed Δ4 desaturase activity. The cloning and characterisation of desaturases from these fish is an important advance, as they are species in which there is a relative wealth of data on the nutritional regulation of ...